Analysis Of Coherence Through Thematic Progression In The Undergraduate Thesis Background Written By English Education Students Of HKBP Nommensen Medan University - Silvia Lestari Hutasoit; Fenty Debora Napitupulu; Febrika Dwi Lestari (Universitas Pahlawan Tuanku Tambusai, 2023)
This study focuses on understanding the kinds of theme progression and degree of coherence in the undergraduate thesis background of English Education students at HKBP Nommensen Medan University. The hypothesis Eggins (2004) developed was applied in this study's descriptive qualitative method. The data source was 10 manuscripts of undergraduate thesis background of English education students from the University of HKBP Nommensen Medan from 2021 - 2022. Meanwhile, the data of this research were the clauses that contain themes and rheme in the undergraduate thesis background. Data collection is done by documentation. The results of the study showed that there are three types of thematic progression: Reiteration/Constant Theme Pattern (68%), Zig-Zag / Linear Theme Pattern (30%), and Multiple Theme Pattern (2%). The level of coherence of the thesis background is 'fair'. These results conclude that thematic progression can be a device to measure students' writing coherence.